2016
DOI: 10.1007/s10018-016-0153-6
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of environmental factors on harvest: the French Guiana shrimp fishery paradox

Abstract: The purpose of this paper is to investigate the environmental nature of the French Guiana shrimp fishery dynamics through an empirical analysis. To do so, we specify a global harvest production function, in which the output depends on the number of days at sea and the stock level. In addition, we use some environmental variables representing the 'El Niño' and 'la Niña' phenomena, the sea surface temperature, and the flow of some Amazonian rivers as instruments. This method enables us to correct the well-known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Such a case study is challenging, because the shrimp stock is declining despite strong reductions in fishing effort over the past two decades. The negative role of external drivers including climate warming is thus put forward (Sanz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a case study is challenging, because the shrimp stock is declining despite strong reductions in fishing effort over the past two decades. The negative role of external drivers including climate warming is thus put forward (Sanz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In order to do so, we analyse the case of the French Guiana shrimp fishery (FGSF), a challenging task since, despite major reductions in fishing effort and harvest levels over the past two decades, the shrimp stock continues to decrease, which suggests that other factors may have a stronger influence on that fishery. Accordingly, the dynamic bioeconomic model developed in this paper considers that the shrimp stock's growth function depends on sea surface temperature (SST), as suggested in Sanz et al (2017).…”
mentioning
confidence: 99%
“…Research showed that sea surface temperature increased, sea surface currents changed and the peak of phytoplankton production (bloom intensity) decreased off the coast of French Guiana over the period of interest. Some new empirical results brought some more evidence of environmental impacts of shrimp stock and production in French Guiana (Sanz et al, 2017;Diop et al, 2018aDiop et al, , 2018b. However, causal relationships between these environmental changes and the evolution of shrimp recruitment have not yet been formally identified.…”
Section: Observed Trajectories Between 2006 and 2014mentioning
confidence: 99%
“…Usually, the production function used in bio-economic literature for fisheries is the socalled Schaefer model where catches depend linearly on both fishing effort and stock. Here we depart from the usual approach by considering the Cobb-Douglas form as in Clark (1990) and Sanz et al (2017):…”
Section: The Production Functionmentioning
confidence: 99%
“…This suggests that other factors may have a stronger influence on the evolution of the FGSF. River flow rate, Niño/Niña phenomena and sea surface temperature (SST) has been shown as the more important factors negatively affecting the productivity of FGSF (Diop et al, 2018;Sanz et al, 2017). The SST has increased between 1970 and 2004 on the Guiana coast.…”
Section: Introductionmentioning
confidence: 99%